Transformasi Pendidikan Berbasis Teknologi sebagai Implementasi SDGs 4 di Era Revolusi Industri 4.0 - Selpi Amanda Fadillah; Dian Misdiyana; Agus Pramono (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Technology-based educational transformation has become an important strategy for achieving Sustainable Development Goal (SDG) 4, which emphasizes inclusive, equitable, and Quality Education for all in the era of the Industrial Revolution 4.0 and digital society. The integration of technology into educational systems is increasingly recognized as a key driver for improving learning outcomes, expanding educational opportunities, and fostering innovation in teaching and learning processes. This study aims to analyze the role of technology in enhancing educational quality and to identify the challenges associated with its implementation. The research employed a literature review approach by examining and synthesizing findings from relevant scientific journals, books, and policy documents. The findings indicate that technologies such as Learning Management Systems (LMS), online learning platforms, digital learning media, and Artificial intelligence (AI) can significantly improve learning effectiveness, support personalized learning experiences, increase accessibility, and promote lifelong learning. Furthermore, technology enables greater flexibility in educational delivery and facilitates collaboration among learners and educators. However, several challenges remain, including unequal digital infrastructure, limited digital literacy and competencies among stakeholders, and socioeconomic disparities that affect access to technology. Therefore, collaboration among governments, educational institutions, educators, students, and communities is essential to strengthen digital infrastructure, improve digital competencies, and develop adaptive educational systems. Technology-based educational transformation can serve as a strategic pathway toward achieving Quality Education and supporting the realization of SDG 4.